Duplication of 17q11.2 and Features of Albright Hereditary Osteodystrophy Secondary to Methylation Defects within the GNAS Cluster: Coincidence or Causal?. (14th January 2013) - White, M.; Conroy, J.; Bullman, H.; Lever, M.; Daly, E.; Betts, D. R.; Cody, D.; Crolla, John A.; Lynch, S. A.
Abstract : We report a case of Albright hereditary osteodystrophy (AHO) in a three-year-old girl with a microduplication at 17q11.2. The child developed obesity within the first 6 months of life. A diagnosis of Albright was made at age 2 years when biochemical evidence of parathyroid resistance was found. No mutations were identified in guanine nucleotide-binding protein G (s) subunit alpha (GNAS1). Subsequent investigations revealed methylation disturbance at GNAS1A, neuroendocrine secretory protein antisense (NESPAS) and neuroendocrine secretory protein 55 (NESP55) confirming a diagnosis of pseudohypothyroidism type 1B. A deletion of NESP55 and uniparental disomy chromosome 20 were excluded which suggested that the features of AHO arose through a purely epigenetic mechanism. Further investigation revealed a de novo microduplication at 17q11.2 encompassing the neurofibromatosis type 1 (NF1) gene. The combination of two rare de novo events in the same child raises the possibility that duplication of a gene within the 17q11.2 region may have triggered abnormal methylation in the GNAS cluster region on chromosome 20.